Cold In-Place Recycling Moisture-Related Design and Construction Considerations for Single or Multiple Component Binder Systems. Issue 1 (2016) - Cox, Ben C.; Howard, Isaac L.; Campbell, Colin S.
In recent years, cold in-place recycling (CIR) has gained momentum because of its economic, performance, and sustainability characteristics; as a result CIR markets are likely to expand into, for example, higher traffic routes. To further understand how to continue improving CIR for existing applications as well as future applications, better techniques are needed with regard to interfacing design and construction. Moisture is one key area in which design and construction are often disconnected. This study's objective, therefore, was to evaluate the moisture (and associated early-age strength and stability) aspects of CIR, particularly within a framework that could consider hydraulic cement, bituminous emulsion, or combinations of both binders. A universal design framework that accommodates any binder or combination thereof while representing early-age field conditions has advantages for agencies, not only in its reasonable characterization of construction processes, but also in its facilitation of competition and creativity in the process of selecting materials and proportions. This study was organized in three phases. Phase 1 documented moisture instrumentation of a cement CIR project. Data were successfully obtained throughout compaction and curing and were used in Phases 2 and 3 alongside supplemental field and laboratory testing. Phase 2 evaluated moisture's role in compaction; Phase 3 evaluated moisture–strength and moisture–stability relationships for various curing protocols. Phase 2 concluded that high (>6%) moisture content, typical of Proctor compaction, is generally unnecessary. Thus, Proctor compaction is discouraged in favor of a fixed design moisture content. Phase 3 concluded that humid (35% to 50% humidity) and dry 40°C oven curing protocols are candidates for universal CIR design.